Checking the fact-checker. Political verification practices and partisan bias in Newtral (Spain) - García-Marín, David (2023)
In recent years, fact-checking journalism has become one of the dominant strategies to tackle disinformation. For these entities to be effective and gain the trust of citizens, it is essential that they carry out their work under the principles of ideological neutrality, especially when they try to verify political discourse. This paper, groundbreaking in the Spanish context, aims to analyze the verification practices and possible partisan biases of political fact-checking in Spain through a specific study applied to Newtral, the main fact-checker specialized in politics in this country. The political verification practices used by this fact-checker since the beginning of its activity (October 2018-October 2022) were analyzed through quantitative content analysis. In a second phase, the same study was replicated, applied only to the discourse of the main national political leaders. The study used inferential statistics (chi-square hypothesis tests, correlational studies, Kruskal-Wallis test and Mann-Whitney U test). No significant differences were observed between political parties in any of the variables analyzed in the phases of execution and verdict, neither in the general sample nor in the specific sample related to political leaders. However, greater attention is paid to the statements made by politicians belonging to Partido Popular, whose discourse is more checked, which could indicate a certain selection bias.